Effects of age, competitive level and perceived moral atmosphere on moral functioning of soccer players - Romand, P.; Pantaloen, N.; d`Arripe-Longueville, F. (International Journal of Sport Psychology, 2009)
The purpose of this study was to examine the effects of age, competitive level and perceived moral atmosphere on the moral functioning (i.e., moral judgment, moral reasons and moral intention) of soccer players. A total of 219 male players, from 8 to 25 years old, participated in the study. Multivariate analyses of variance revealed significant differences in the three variables of interest as a function of age, and significant differences in moral judgment and intention as functions of competitive level and perceived moral atmosphere. These results are discussed in relation to the "theory of game reasoning" (Shields & Bredemeier, 1995) and the current moral development literature. The nature of moral indicators and the precautions that need to be taken in studies of moral functioning are also highlighted. Finally, the limitations of the study and recommendations for future directions are presented.